DESIGN THINKING IN TEACHER PROFESSIONAL DEVELOPMENT: A TRANSDISCIPLINARY APPROACH TO CURRICULUM INNOVATION - Raihana, Esti; Ramlan, Ramlan; Leisthari, Fepi (CV. Lafadz Jaya, 2025)
This research aims to explore the role of a design thinking approach in teacher professional development as a transdisciplinary strategy to foster curriculum innovation. Using a literature review, this research examines various academic sources and empirical studies that discuss the integration of design thinking in educational contexts, particularly in teacher training and capacity development. Findings indicate that design thinking not only enhances teachers' ability to design relevant and creative learning experiences but also fosters cross-disciplinary collaboration, empathy for student needs, and increased flexibility and responsiveness to curriculum change. This approach strengthens teachers' position as adaptive and reflective learning designers in facing the complex challenges of the 21st century. Therefore, adopting design thinking in teacher professional development programs is considered strategic for generating contextual and sustainable curriculum innovation.